Effectiveness of parental sugar java turmeric drink (curcuma tamarindus) on menstruation pain in adolesce - Safitri, Mey Elisa; Maryanti, Endang; Juliani, Sri; Sembiring, Julina Br (Journal of Midwifery and Nursing, 2024)
Dysmenorrhea is a symptomatic phenomenon including abdominal pain, cramps and back pain. The aim of this study was to analyze the effectiveness of the palm sugar turmeric drink (Curcuma Tamarindus) on menstrual pain in adolescent girls in Sei Mencirim Village, Sunggal District, Deli Serdang Regency. The research design uses a quasi-experimental design research method, Posttest-Only Control Design type, namely there are two groups, each selected randomly (R). The first group was given treatment (X) and the other group was not. The group that is treated is called the experimental group and the group that is not treated is called the control group. The population in this study were 20 teenagers who experienced menstrual pain who were divided into two groups and observed for 4 days starting from the first day of menstruation. In this study, the effect of treatment was analyzed using the Non-Parametric Independent Sample T test (man Whitney U) in SPSS with version 17, the result was p = 0.001 where p < 0.05, which means there was a difference in pain reduction in the control group and the treatment group, where In the treatment group, almost all or 78.6% of the pain was reduced on the 2nd day of menstruation. The research output will be published in a reputable national journal and the expected results in this research will be a reduction in the scale of pain in adolescents during menstruation so that there are no longer obstacles to activities in adolescents caused by pain during menstruation